Analisa Perancangan Dinding Penahan Tanah terhadap Stabilitas dan Daya Dukung Tanah Bandara - Virma Septiani; Sukahir; Viktor Suryan; Afra Nabilah Andeni (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
A retaining wall design is a construction design that functions to retain loose or natural soil and prevent the collapse of sloping land or slopes whose stability cannot be guaranteed by the slope of the land itself. The retained soil provides an active push on the wall structure so that the structure is less likely to topple or shift. Initially, retaining walls were made due to the increasing use of retaining construction which was used as a place to store or store materials in granular form. A mockup is an imitation of an object in a shape that is exactly the same as the original shape with a size that is smaller than the actual size. Mockups are usually made on a smaller scale than the original object and aim to help visualize, understand and test concepts. The aim of this research is to analyze the design of retaining walls where the design of retaining walls functions to retain loose or natural soil and prevent the collapse of sloping soil whose stability cannot be guaranteed by the slope of the soil itself. Based on the results of the design analysis of the design of the retaining wall, the results of the design calculation analysis of the active load were 90.07 tons and the passive load was 126.38 tons. The results of the passive load calculation were greater than the active load so that it was considered effective and relatively safe for supporting the surface of the land. landslides supported by walls. The results of the mock-up design can be assumed to be of a suitable size and calculation to be used for realization in accordance with the designation of the retaining wall.